A projection of changes in landfalling atmospheric river frequency and extreme precipitation over western North America from the Large Ensemble CESM simulations. Issue 3 (6th February 2016) - Hagos, Samson M.; Leung, L. Ruby; Yoon, Jin‐Ho; Lu, Jian; Gao, Yang
Abstract: Simulations from the Community Earth System Model (CESM) Large Ensemble project are analyzed to investigate the impact of global warming on atmospheric rivers (ARs) making landfall in western North America. The model has notable biases in simulating the subtropical jet position and the relationship between extreme precipitation and moisture transport. After accounting for these biases, the model projects an ensemble mean increase of 35% in the number of landfalling AR days between the last 20 years of the twentieth and 21st centuries under Representative concentration pathway 8.5 (RCP8.5). However, the associated extreme precipitation days increase only by 28% because the moisture transport required to produce extreme precipitation also increases with warming. Internal variability introduces an uncertainty of ±8% and ±7% in the changes in AR days and associated extreme precipitation days compared to only about 1% difference from accountings for model biases. The significantly larger mean changes compared to internal variability, and effects of model biases highlight the robust AR responses to global warming. Key Points: ARs and related extreme precipitation days will increase with global warming The model response is larger than the uncertainty from bias and natural variability Increase in the frequency of AR extreme precipitation days is smaller than in AR days